Targeted ablation of IKK2 improves skeletal muscle strength, maintains mass, and promotes regeneration - Mourkioti, Foteini (American Society for Clinical Investigation, 2006)
NF-κB is a major pleiotropic transcription factor modulating immune, inflammatory, cell survival, and proliferative responses, yet the relevance of NF-κB signaling in muscle physiology and disease is less well documented. Here we show that muscle-restricted NF-κB inhibition in mice, through targeted deletion of the activating kinase inhibitor of NF-κB kinase 2 (IKK2), shifted muscle fiber distribution and improved muscle force. In response to denervation, IKK2 depletion protected against atrophy, maintaining fiber type, size, and strength, increasing protein synthesis, and decreasing protein degradation. IKK2-depleted mice with a muscle-specific transgene expressing a local Igf-1 isoform (mIgf-1) showed enhanced protection against muscle atrophy. In response to muscle damage, IKK2 depletion facilitated skeletal muscle regeneration through enhanced satellite cell activation and reduced fibrosis. Our results establish IKK2/NF-κB signaling as an important modulator of muscle homeostasis and suggest a combined role for IKK inhibitors and growth factors in the therapy of muscle diseases.